Pet Feeding System - Che Hasni, Helmi; Suhaimi, Suhazlan (International Journal of Recent Technology and Applied Science (IJORTAS), 2022)
The objective of this research is to design an IoT (Internet of Things) that can enhance pets care and monitoring. Keeping pets has become a popular among people at the present and one of the best companions that available at home. Taking care pets need effort and time and most of the owner having problem because of their busy schedules. By utilizing the microcomputer and internet, this research will be able to feed and monitoring the pets when owner is away from their pets. We develop the prototype of food dispenser modified with servo motor, webcam, and raspberry pi. A web application is developed to control the servo motor and webcam by sending signal to the raspberry pi. To conclude, from the research we found out 79% respondents strongly agree that pet feeding system are useful and 61% want to buy the system. In future, we hope that feeding system can be apply to animals in the zoo, pet shop, wildlife department, etc.